Canoe slalom competition analysis - Hunter, A.; Cochrane, J.; Sachlikidis, A. (Sports Biomechanics, 2008)
The aim of this study was to quantify the differences between groups of elite canoe slalom athletes based on the class they paddle in and the strategies they use in competition. Canoe and kayak footage was recorded using three cameras and analysed using lapsed-time time-motion analysis. Analysis was undertaken on the ten fastest competition runs for men's kayak and canoes and women's kayak for the 22-gate semi-final/final course at the 2005 canoe slalom world championships. Comparison between the categories of paddlers revealed that despite canoe paddlers taking significantly (P < 0.05) fewer strokes than kayak paddlers., they were not significantly slower than men's single kayak paddlers with respect to their run times and only significantly slower between 4 of 22 gates. Results revealed also that paddlers using different turn strategies (spin vs. pivot) had significantly (P < 0.05) different split times for the gates before and after the execution of the manoeuvre. For a paddler this means that their individual strategy could be analysed and compared with those of others to determine if alternate strategies would be beneficial to their performance.